2020
DOI: 10.1080/1540496x.2020.1785865
|View full text |Cite
|
Sign up to set email alerts
|

COVID–19’s Impact on Stock Prices Across Different Sectors—An Event Study Based on the Chinese Stock Market

Abstract: In this article, we use an event study approach to empirically study the market performance and response trends of Chinese industries to the COVID-19 pandemic. The study found that transportation, mining, electricity & heating, and environment industries have been adversely impacted by the pandemic. However, manufacturing, information technology, education and health-care industries have been resilient to the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
349
7
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(488 citation statements)
references
References 37 publications
(22 reference statements)
30
349
7
17
Order By: Relevance
“…In line with the risk-return hypothesis, we construct a predictive model that quantifies the response of the Asia-Pacific Islamic stock market as well as the conventional market to UPE. During turbulence, a number of studies have established a negative correlation between risk and market returns for conventional stocks (see Al-Awadhi et al, 2020;He et al, 2020;Phan & Narayan, 2020;Salisu & Akanni, 2020) and a positive correlation for Islamic stocks (see Masih et al, 2018). To circumvent any potential endogeneity bias and persistence effect, the predictive model takes the form (see Westerlund & Narayan, 2012:…”
Section: Data and Methodsology II Data And Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the risk-return hypothesis, we construct a predictive model that quantifies the response of the Asia-Pacific Islamic stock market as well as the conventional market to UPE. During turbulence, a number of studies have established a negative correlation between risk and market returns for conventional stocks (see Al-Awadhi et al, 2020;He et al, 2020;Phan & Narayan, 2020;Salisu & Akanni, 2020) and a positive correlation for Islamic stocks (see Masih et al, 2018). To circumvent any potential endogeneity bias and persistence effect, the predictive model takes the form (see Westerlund & Narayan, 2012:…”
Section: Data and Methodsology II Data And Methodsologymentioning
confidence: 99%
“…In this paper, we examine the potential of the Asia-Pacific Islamic stock market to serve as a good hedge against uncertainty due to pandemics and epidemics (UPE). The study's motivation has roots in the extant literature, which suggests a strong connection between the COVID-19 pandemic and conventional stocks (see, for example, Al-Awadhi et al, He et al, 2020;Phan & Narayan, 2020;Salisu & Akanni, 2020). Yet, the responsiveness of Islamic stock markets to COVID-19 seems relatively understudied (Ashraf et al, 2020).…”
Section: Introduction I Introductionmentioning
confidence: 99%
“…The occurrence of SARS-CoV-2 virus influenced the economic setting and marked investor sentiment, also triggering stock price fluctuations [15]. Yilmazkuday [68] exhibited that an upsurge in daily total fatalities due to SARS-CoV-2 will lessen the international economic activity assessed through by the Baltic Exchange Dry Index.…”
Section: Prior Research Regarding the Economic And Financial Consequementioning
confidence: 99%
“…Fallahgoul [81] established that the financial segment is the most doubtful, whereas health is the most hopeful over the COVID-19 pandemic. He, Sun, Zhang and Li [15] claimed that manufacturing, information technology, education and health-care Chinese sectors remained stable to COVID-19. Gu, et al [82] found that Chinese manufacturing sector was hardly hit by corona crisis, but construction, information transfer, computer services and software, and health care and social work were positively influenced by COVID-19.…”
Section: Prior Research Regarding the Economic And Financial Consequementioning
confidence: 99%
“…The existing literature on the impact of COVID-19 is evolving. The literature has found that the pandemic adversely impacts economic growth and trade (Vidya & Prabheesh, 2020) and stock markets (Ertuğrul et al, 2020;Haroon & Rizvi, 2020;He et al, 2020;Huang & Zheng, 2020;Iyke, 2020;Phan & Narayan, 2020;. However, no specific study examines the FPI and stock market returns relationship during the COVID-19 pandemic.…”
Section: Introduction I Introductionmentioning
confidence: 99%